Trans-Nasion-Complex Approach for Endoscopic Modified Lothrop Procedure: Conception, Anatomy, and Technique - Zhao, Yu; Liu, Jianfeng; Yang, Dazhang; Han, Jun; Zhao, Jianhui; Wang, Yibei (Frontiers in Surgery, 2022)
Background The endoscopic modified Lothrop procedure (EMLP) is an important procedure used to address frontal and anterior skull-base lesions. Two techniques were established, namely, the inside-out approach and the outside-in approach. The former technique take the frontal recess and the first olfactory filament (FOF) as key landmarks while the latter use the FOF as posterior boundary. In some cases, however, these two landmarks are not available. Therefore, we supplement the outside-in approach and named it trans-nasion-complex approach (TNCA) for EMLP that can be performed without locating these two landmarks. Methods Two dry human skulls were used to observe the bony nasion complex. Then, five colored silicon-injected human head specimens were dissected via TNCA for EMLP. Finally, the outcomes of patients who underwent TNCA were reviewed. Results The nasion complex is an osseous complex that consists of the nasion and its adjacent structures, including the bilateral root of nasal bones, nasal process of frontal bones, anterior portion of the perpendicular plate of the ethmoid bone that connects with the inferior aspect of the nasal bones, and portions of the bilateral frontal process of the maxillary bones. Surgical landmarks for TNCA include the anterior superior portion of the nasal septum, anterior margin and axilla of the middle turbinate, frontal process of the maxilla bone, nasal process of the frontal bone and upper part of the nasal bone. These structures form a “mushroom sign” during cadaveric dissection and surgery. Twenty-one patients underwent TNCA, of whom 9 had tumors and 12 had chronic rhinosinusitis with nasal polyps (CRSwNP). None of them had major complications. Conclusion TNCA is expected to be a safe, and direct route for EMLP. Adequate understanding of the nasion complex and “mushroom sign” will be helpful to complete TNCA.